2005
DOI: 10.1111/j.1365-2109.2004.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen budget and fluxes in Colossoma macropomum ponds

Abstract: This study quanti¢ed the accumulation of nitrogen (N) in the water column, sediments, ¢sh and seepage water during a production cycle of Colossoma macropomum. By combining estimates of the deposition rates of uneaten feed, faeces and dead phytoplankton with measurements of N accumulation in the sediment, the rate of decomposition of organic matter in the sediment was estimated. The ¢rst-order rate constant for organic matter decomposition was 0.237 AE 0.019 day À1 . Total N recovery during the ¢rst weeks of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
(33 reference statements)
1
14
3
Order By: Relevance
“…The survival rates obtained in all treatments in this study (>90%) are similar to those obtained during tambaqui grow‐out periods in ponds obtained by other authors (Melo et al 2001; Izel & Melo 2004; Jimenéz‐Montealegre, Avnimelech, Verreth & Verdegem 2005). This confirms that tambaqui adapts well to pond conditions under a range of management regimes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The survival rates obtained in all treatments in this study (>90%) are similar to those obtained during tambaqui grow‐out periods in ponds obtained by other authors (Melo et al 2001; Izel & Melo 2004; Jimenéz‐Montealegre, Avnimelech, Verreth & Verdegem 2005). This confirms that tambaqui adapts well to pond conditions under a range of management regimes.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, fish from Lim and LimFer treatments grew to more than 1 kg during the rearing period and the final weights (>1 kg) were well acceptable by the market standard. The SGR in this study is lower than that obtained by Jimenéz‐Montealegre et al (2005) (2.89%) during tambaqui rearing in ponds for 111 days. The SGR during the grow‐out phase was also lower than obtained by Silva, Gomes and Roubach (2007) during tambaqui juvenile production in ponds (8–10%) and by Silva, Gomes and Brandão 2007 in cages (4.40–6.30%).…”
Section: Discussioncontrasting
confidence: 82%
“…Oxygenated bottom sediments benefit water conditions by oxidizing and detoxifying anaerobic metabolites before diffusing into the water column. Previous studies have also shown conditions in the upper layers of bottom sediments to undergo changes due to an increase in Amazon river prawn stocking density and swimming activity (Kimpara, Moraes‐Valenti, Queiroz, & New, ), and the foraging behavior of the tambaqui was suggested to reduce total ammonia nitrogen in the bottom sediments through bioturbation (Jiménez‐Montealegre, Avnimelech, Verreth, & Verdegem, ). The IMTA of the present study showed an increase in settleable solids (~23 g SS/m 2 day −1 ) when compared to the tambaqui monoculture (~5 g SS/m 2 day −1 ) perhaps due to the bioturbation from the animals of both trophic levels.…”
Section: Discussionmentioning
confidence: 95%
“…Feed usually accounts for the most nitrogen in semi‐intensive aquaculture. Feed nitrogen has accounted for ~95%–97% of all inputs for the semi‐intensive grow‐out of the Giant river prawn (Adhikari et al, ; Sahu et al, ), ~88% for Channel catfish ( Ictalurus punctatus ) monoculture (Gross et al, ), 91% for Nile tilapia monoculture (Acosta‐Nassar, Morell, & Corredor, ), and 97% for tambaqui monoculture (Jiménez‐Montealegre et al, ). In the IMTA of the Amazon river prawn and the Nile tilapia, feed accounted for ~ 65%–71% of all nitrogen inputs (David et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Jimenez‐Montealegre et al (2005) obtained pore water by centrifugation of the top 5 cm layer of pond sediments. This method allows for direct sampling of pore water, but obtaining soil cores from ponds and centrifuging the samples is both tedious and time consuming.…”
Section: Mean (±Sd) Water Volume and Quantity Of Nutrient Loss (G) Tmentioning
confidence: 99%